On the Prime Radical of Nearrings which is Kurosh-Amitsur (European Journal of Pure and Applied Mathematics, 2024)
A prime radical of near-rings is introduced by defining a new class of prime modules of near-rings. It is a generalization of the Prime radical of rings. Properties of the radical are studied. It is established that this radical is a Kurosh-Amitsur radical of near-rings.
Keywords: near-ring; N-group; primeN-groups of type 2; Prime radical of type 2